Prof.K.H. Yudian Wahyudi, Ph.D Cendekiawan Muslim Kelas Dunia: komparasi dengan Ahmad Khan, Yusuf Al-Qaradhawi, Ali Shari'ati dan Nashr Hamid Abu Zayd - Kholfa Zubair Taqo Sidqi (Iqralana, 2023)
wd-5/wd,c.1-5